Exploring Health Seeking Behavior among Rural Men in Punjab, Pakistan: Insights from HealthCare Providers - Mushtaq, Shahzad Khaver; Yasin, Ghulam; Yunus, Asma (Annals of Human and Social Sciences, 2024)
This study explores healthcare providers’ perspectives to identify the socio-demographic, economic, cultural and health system factors shaping health-seeking behavior of rural male population. Pakistan is facing several challenges due to epidemiological transition. Although progress has been made, Pakistan’s health status, especially of rural population is falling behind in the region. Exploring the factors of health seeking behavior of rural male population can yield critical roadmap for improving health outcomes in these communities. The data is collected through in-depth interviews of nine healthcare providers from various healthcare provision systems in the locale. Braun & Clarks approach of thematic analysis is used to analyze data. The analysis reveals key barriers such as financial constraints, educational deficits, cultural beliefs, and inadequate health infrastructure are identified by healthcare providers. The need for qualified medical personnel and essential medicines has inversely affected healthcare utilization. This study provides valuable insights for policymakers highlighting the need to develop and implement culturally sensitive health promotion strategies.